NON-EQUIVALENCE TRANSLATION AT WORD LEVEL FROM MANDARIN TO INDONESIAN IN HIGHSCHOOL/MA MANDARIN TEXTBOOK - Gustini Wijayanti (Fakultas Sastra Universitas Darma Persada, 2020)
This research aimed to analyze the non-equivalence translation at the word level, including translation strategy to solve the non-equivalence translation result from Mandarin to Indonesian in the Highschool/MA Mandarin textbook published Depdikbud. This research used the qualitative research method. This research proves 24 non-equivalence translation data from the source language (Mandarin) to the target language (Indonesian) at the word level. Non-equivalencies in the translation from Mandarin to Indonesian are caused by the misunderstanding word, phrases, or expressions in the source language. The translator can use the strategy to get the equivalent translation at the word level primarily by using the more familiar word and closer to the level from the source language (Mandarin) and using paraphrase.